Understanding oriental and western dragons in a globalised world: a cross-linguistic study of dragon-based metaphorical expressions in Chinese and English - Meow, Ee Chew; Lay, Shi Ng; Nurjanah Mohd Jaafar,; Chun, Keat Yeap (Penerbit Universiti Kebangsaan Malaysia, 2024)
Animal metaphors are widely utilised across diverse linguistic landscapes and transcend cultural boundaries. This paper examines the relationship between culture and linguistic expressions by analysing metaphors in the idioms and proverbs of two typologically different languages: Chinese and English. The objective is to explore the variations in the use of the dragon as a conceptual metaphor in these two languages. Data were collected from two online platforms: Chinese-Tools.com and The Free Dictionary. A comparative analysis was performed, structured in several steps: data organisation and categorisation, followed by quantitative and qualitative analyses and concluded with a cross-cultural comparison. This methodology allowed for the identification of similarities and differences in dragonbased metaphorical expressions. A conceptual mapping model was also used to examine the variations between Chinese and English in conceptualising the human domain using dragons as the source domain. The findings reveal that the mapping of dragon characteristics onto human beings varies, encompassing behaviours, appearances, and intellectual competency. Chinese dragon metaphors generally carry positive meanings, while negative meanings are more prominent in English dragon metaphors. This contrast can be attributed to the dragon’s representation as an auspicious creature symbolising power and wisdom in Chinese culture, whereas it is associated with malevolence and destruction in English culture. These findings have implications for cross-cultural communication and understanding, especially as the world becomes increasingly interconnected through globalisation. The exchange and adaptation of cultural symbols, including metaphors, have accelerated across linguistic and cultural boundaries.